MOF-based low-boiling-point VOCs adsorbent and preparation method thereof
By combining iron-based MOF with zirconium-based MOF and fixing it on the surface of glass fibers to form a MOF wheel, the problems of insufficient adsorption performance and poor structural stability in traditional zeolite wheels when dealing with low boiling point VOCs are solved, and higher adsorption capacity and selectivity, as well as better structural stability are achieved.
Patent Information
- Application Number
- CN202510121512.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional zeolite runners have insufficient adsorption performance and poor structural stability when dealing with low boiling point VOCs. Especially under high temperature or high airflow conditions, the adsorption efficiency is significantly reduced.
Using a low boiling point VOCs adsorbent based on MOF, the MOF is formed by compositeing iron-based MOF with zirconium-based MOF and fixing it to the surface of the glass fiber using a modified binder.
It significantly improves adsorption capacity and selectivity, enhances the bonding force between the MOF and the rotor, improves the thermal and chemical stability of the material, extends service life and reduces maintenance costs.
Smart Images

Figure BDA0005258996630000111 
Figure BDA0005258996630000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbents, and in particular to a MOF-based low-boiling-point VOCs adsorbent and a preparation method thereof. Background Art
[0002] Zeolite wheel adsorption concentration technology is one of the mainstream technologies for treating industrial VOCs. It converts high-volume, low-concentration VOCs waste gas into low-volume, high-concentration waste gas, significantly reducing the operating cost and energy consumption of subsequent treatment equipment. However, in actual application, this technology also has some obvious technical limitations.
[0003] First, for specific exhaust gas components, such as low-boiling point VOCs (such as ethanol, ethyl acetate, etc.), the adsorption capacity and selectivity of traditional zeolite wheels are often insufficient. These low-boiling point VOCs have low boiling points, high volatility, small molecular size and some strong polarity, so they have weak adsorption interactions with zeolite pores and are easy to desorb, especially under high temperature or high airflow conditions, where the adsorption efficiency drops significantly. In addition, the adsorption selectivity of the pore structure of zeolite for low-boiling point VOCs needs to be improved, especially in complex mixed gas environments, where the competition for active adsorption sites makes it difficult for zeolite to preferentially adsorb target VOCs molecules, thereby affecting the overall adsorption performance.
[0004] Secondly, in traditional zeolite wheels, the insufficient bonding force between the loaded zeolite adsorbent material and the wheel substrate (such as glass fiber, ceramic or metal substrate) is another major challenge faced by wheel technology in practical applications. The adsorbent material loaded in the wheel is usually in powder form and needs to be fixed to the surface of the substrate by a binder to form a wheel structure. However, the interface compatibility between traditional binders and adsorbent materials is poor, which causes the adsorbent to easily fall off the surface of the substrate, especially under conditions of high-speed rotation or high airflow impact. This problem of insufficient bonding force will not only reduce the adsorption performance of the wheel, but also shorten its service life and increase maintenance costs.
[0005] In recent years, metal organic framework materials (MOF) have been considered as one of the ideal materials for adsorbing VOCs due to their high specific surface area, adjustable pore structure and excellent chemical stability, and have shown great application potential in the fields of air purification, industrial waste gas treatment and environmental protection. Especially in the treatment of low-boiling point VOCs (such as formaldehyde, acetone, benzene series, etc.), MOF materials can achieve efficient capture and selective adsorption of target molecules with their unique pore structure and surface chemical properties.
[0006] In summary, in order to solve the problems of insufficient adsorption performance and poor structural stability of the traditional zeolite wheel when treating low-boiling point VOCs, the present application prepares a MOF-based low-boiling point VOCs adsorbent. Summary of the invention
[0007] The object of the present invention is to provide a MOF-based low-boiling-point VOCs adsorbent and a preparation method thereof, so as to solve the problems raised in the prior art.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a low-boiling-point VOCs adsorbent based on MOF comprises the following steps:
[0010] Step 1: Mix ferric chloride hexahydrate, PEO-PPO-PEO (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), and deionized water, stir evenly, then add glacial acetic acid, terephthalic acid and 2-aminoterephthalic acid, continue to stir evenly, heat to 110-120°C, keep warm for 12-13h, cool, centrifuge, wash, and vacuum dry to obtain iron-based MOF powder;
[0011] Step 2: Dissolve zirconium chloride in N,N-dimethylformamide, add concentrated hydrochloric acid to adjust the acidity of the reaction system, stir ultrasonically until completely dissolved, then add 2-aminoterephthalic acid and iron-based MOF powder, stir evenly, heat to 80-90°C, react for 24-25h, cool to room temperature, and centrifuge to obtain dual MOF powder;
[0012] Step 3: Add the dual MOF powder to the water-based epoxy resin emulsion, apply it to the surface of the glass fiber, and solidify it to obtain a glass fiber semi-finished product, which is then combined and bonded and rolled into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent.
[0013] More optimally, the iron-based MOF powder includes the following substances: ferric chloride hexahydrate, PEO-PPO-PEO, deionized water, glacial acetic acid, terephthalic acid, and 2-aminoterephthalic acid, by weight.
[0014] More optimally, the dual MOF powder includes the following substances: zirconium chloride, N,N-dimethylformamide, 2-aminoterephthalic acid, and iron-based MOF powder in parts by weight.
[0015] More optimally, the mass ratio of the dual MOF powder to the aqueous epoxy resin emulsion is (0.8-0.9):1.
[0016] More optimally, the waterborne epoxy resin emulsion comprises the following substances: by weight, 80-90 parts of waterborne epoxy emulsion, 100-110 parts of modified curing agent, 3-6 parts of coupling agent, and 30-60 parts of water.
[0017] More optimally, the preparation process of the modified curing agent is:
[0018] S1: Mix epoxy resin 6101, polyethylene glycol, dibutyltin dilaurate and diphenylmethane diisocyanate, stir evenly, heat to 90-95°C, react for 4-5h, and cool to room temperature to obtain polyurethane epoxy resin;
[0019] S2: 3-(carboxymethyl)benzoic acid and 4,7,10-trioxytridecyl-1,13-diamine were mixed, stirred and heated to 200-220°C, reacted for 4-5h, and distilled under reduced pressure until no obvious bubbles were found, the reaction was stopped, and cooled to room temperature to obtain a rigid polyetheramine;
[0020] S3: Mix the polyurethane epoxy resin and the rigid polyetheramine, stir and heat to 80-90°C, react for 4-5 hours, and cool to room temperature to obtain a modified curing agent.
[0021] More optimally, the polyurethane epoxy resin comprises the following substances: by weight, 60-70 parts of epoxy resin 6101, 40-45 parts of polyethylene glycol, 0.1-0.2 parts of dibutyltin dilaurate, and 30-40 parts of diphenylmethane diisocyanate;
[0022] The rigid polyetheramine comprises the following substances: 100-120 parts by weight of 3-(carboxymethyl)benzoic acid and 250-280 parts by weight of 4,7,10-trioxytridecyl-1,13-diamine;
[0023] The mass ratio of the polyurethane epoxy resin to the rigid polyetheramine in the modified curing agent is 1:(9-10).
[0024] More optimally, the curing process parameters are: temperature of 50-60°C and time of 24-30h.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention successfully prepared a MOF rotor by compounding iron-based MOF with zirconium-based MOF and fixing it on the surface of glass fiber with a binder, making it act as a VOCs adsorbent. This design significantly improves the adsorption capacity and selectivity. At the same time, by modifying the epoxy resin binder, the binding force between MOF and the rotor is effectively enhanced, thereby further expanding the application scenarios of the prepared VOCs adsorbent. The details are as follows:
[0027] First: The composite material of iron-based MOF and zirconium-based MOF has significant beneficial effects in the adsorption of VOCs gases. First, the composite structure of iron-based MOF and zirconium-based MOF can fully utilize the advantages of both: the iron-zirconium dual MOF has good adsorption activity and adjustable pore structure, while the introduction of zirconium-based MOF further improves the thermal stability and chemical stability of the dual MOF. This composite structure not only increases the specific surface area and porosity of the material, but also increases the adsorption capacity of VOCs through synergistic effects, and ensures the long-term use of the material in high humidity or complex environments; secondly, the richer active sites of the iron-zirconium dual MOF can form stronger interactions with VOCs molecules, thereby enhancing the adsorption selectivity of VOCs molecules. This composite material exhibits higher adsorption efficiency and lower penetration when adsorbing VOCs, and is particularly suitable for treating low-concentration, multi-component VOCs;
[0028] Second: In the scheme, the synergistic effect of the flexible segments and rigid segments contained in the modified curing agent makes the cured epoxy resin not only have good flexibility, but also have high strength, and can maintain excellent adhesive properties under complex stress environments. In addition, the aromatic ring structure in the polyetheramine segment further enhances the high temperature resistance of the epoxy resin, making it difficult to soften or decompose under high temperature conditions, thereby significantly improving the bonding ability of the material. At the same time, the amino functional groups in the dual MOF can chemically bond with the active groups (such as epoxy groups) in the epoxy resin, further enhancing the bonding force between the MOF and the glass fiber substrate. This chemical bonding not only improves the interfacial stability of the material, but also improves the overall strength of the cured material through the high mechanical strength of the dual MOF itself; this synergistic effect ensures the high performance and long life of the runner in practical applications, especially when dealing with low-boiling point VOCs. DETAILED DESCRIPTION
[0029] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0030] It should be noted that the following parts are by weight, and the purchase manufacturers of all raw materials involved in the present invention are exemplary without any special restrictions: In the following embodiments, 3-(carboxymethyl)benzoic acid CAS is 2084-13-1; 4,7,10-trioxytridecyl-1,13-diamine CAS is 4246-51-9; PEO-PPO-PEO (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, Ma=5800)
[0031] Example 1: A method for preparing a low-boiling-point VOCs adsorbent based on MOF, comprising the following steps:
[0032] Step 1: Mix 14 parts of ferric chloride hexahydrate, 13 parts of PEO-PPO-PEO, and 350 parts of deionized water, stir evenly, then add 26 parts of glacial acetic acid, 5 parts of terephthalic acid, and 4 parts of 2-aminoterephthalic acid, continue to stir evenly, heat to 110°C, keep warm for 12 hours, cool, centrifuge, wash, and vacuum dry to obtain iron-based MOF powder;
[0033] Step 2: Dissolve 7 parts of zirconium chloride in 70 parts of N,N-dimethylformamide, add concentrated hydrochloric acid to adjust the acidity of the reaction system, and stir ultrasonically until completely dissolved. Then, add 6 parts of 2-aminoterephthalic acid and 3 parts of iron-based MOF powder, stir evenly, heat to 80°C, react for 24 hours, cool to room temperature, and centrifuge to obtain dual MOF powder;
[0034] Step 3: Add 0.8 parts of the double MOF powder to 1 part of the water-based epoxy resin emulsion, apply it to the surface of the glass fiber, and cure it at 60°C for 24 hours to obtain a glass fiber semi-finished product, and combine and bond them, and roll them into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent; the water-based epoxy resin emulsion includes the following substances: 80 parts of water-based epoxy emulsion (GS-730A), 100 parts of modified curing agent, 3 parts of γ-glycidyloxypropyltrimethoxysilane, and 30 parts of water;
[0035] Wherein, the preparation process of the modified curing agent is:
[0036] S1: 60 parts of epoxy resin 6101, 40 parts of polyethylene glycol, 0.1 parts of dibutyltin dilaurate, and 30 parts of diphenylmethane diisocyanate were mixed, stirred evenly, heated to 90°C, reacted for 4 hours, and cooled to room temperature to obtain polyurethane epoxy resin;
[0037] S2: 100 parts of 3-(carboxymethyl)benzoic acid and 250 parts of 4,7,10-trioxytridecyl-1,13-diamine were mixed, stirred and heated to 200°C, reacted for 4 hours, and distilled under reduced pressure until no obvious bubbles were present. The reaction was stopped and cooled to room temperature to obtain a rigid polyetheramine;
[0038] S3: 10 parts of polyurethane epoxy resin and 90 parts of rigid polyetheramine were mixed, heated to 80° C. with stirring, reacted for 4 hours, and cooled to room temperature to obtain a modified curing agent.
[0039] Example 2: A method for preparing a low-boiling-point VOCs adsorbent based on MOF, comprising the following steps:
[0040] Step 1: Mix 15 parts of ferric chloride hexahydrate, 15 parts of PEO-PPO-PEO, and 380 parts of deionized water, stir evenly, then add 28 parts of glacial acetic acid, 6 parts of terephthalic acid, and 5 parts of 2-aminoterephthalic acid, continue to stir evenly, heat to 120°C, keep warm for 13 hours, cool, centrifuge, wash, and vacuum dry to obtain iron-based MOF powder;
[0041] Step 2: Dissolve 10 parts of zirconium chloride in 80 parts of N,N-dimethylformamide, add concentrated hydrochloric acid to adjust the acidity of the reaction system, and stir ultrasonically until completely dissolved. Then, add 7 parts of 2-aminoterephthalic acid and 4 parts of iron-based MOF powder, stir evenly, heat to 90°C, react for 25 hours, cool to room temperature, and centrifuge to obtain dual MOF powder;
[0042] Step 3: Add 0.8 parts of the double MOF powder to 1 part of the water-based epoxy resin emulsion, apply it to the surface of the glass fiber, and cure it at 60°C for 24 hours to obtain a glass fiber semi-finished product, and combine and bond them, and roll them into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent; the water-based epoxy resin emulsion includes the following substances: 80 parts of water-based epoxy emulsion (GS-730A), 100 parts of modified curing agent, 3 parts of γ-glycidyloxypropyltrimethoxysilane, and 30 parts of water;
[0043] Wherein, the preparation process of the modified curing agent is:
[0044] S1: 70 parts of epoxy resin 6101, 45 parts of polyethylene glycol, 0.2 parts of dibutyltin dilaurate, and 40 parts of diphenylmethane diisocyanate were mixed, stirred evenly, heated to 95°C, reacted for 4-5 hours, and cooled to room temperature to obtain polyurethane epoxy resin;
[0045] S2: 120 parts of 3-(carboxymethyl)benzoic acid and 280 parts of 4,7,10-trioxytridecyl-1,13-diamine were mixed, heated to 220°C with stirring, reacted for 5 hours, and distilled under reduced pressure until no obvious bubbles were present. The reaction was stopped and cooled to room temperature to obtain a rigid polyetheramine;
[0046] S3: 10 parts of polyurethane epoxy resin and 100 parts of rigid polyetheramine were mixed, heated to 90° C. with stirring, reacted for 5 hours, and cooled to room temperature to obtain a modified curing agent.
[0047] Example 3: A method for preparing a low-boiling-point VOCs adsorbent based on MOF, comprising the following steps:
[0048] Step 1: 14.5 parts of ferric chloride hexahydrate, 14 parts of PEO-PPO-PEO, and 360 parts of deionized water were mixed and stirred evenly, and then 27 parts of glacial acetic acid, 5.5 parts of terephthalic acid, and 4.5 parts of 2-aminoterephthalic acid were added, and the mixture was stirred evenly, and then heated to 115°C, kept warm for 12.5 hours, cooled, centrifuged, washed, and vacuum dried to obtain an iron-based MOF powder;
[0049] Step 2: Dissolve 8 parts of zirconium chloride in 75 parts of N,N-dimethylformamide, add concentrated hydrochloric acid to adjust the acidity of the reaction system, and stir ultrasonically until completely dissolved. Then, add 6.5 parts of 2-aminoterephthalic acid and 3.5 parts of iron-based MOF powder, stir evenly, heat to 85°C, react for 24 hours, cool to room temperature, and centrifuge to obtain dual MOF powder;
[0050] Step 3: Add 0.8 parts of the double MOF powder to 1 part of the water-based epoxy resin emulsion, apply it to the surface of the glass fiber, and cure it at 60°C for 24 hours to obtain a glass fiber semi-finished product, and combine and bond them, and roll them into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent; the water-based epoxy resin emulsion includes the following substances: 80 parts of water-based epoxy emulsion (GS-730A), 100 parts of modified curing agent, 3 parts of γ-glycidyloxypropyltrimethoxysilane, and 30 parts of water;
[0051] Wherein, the preparation process of the modified curing agent is:
[0052] S1: 65 parts of epoxy resin 6101, 42 parts of polyethylene glycol, 0.15 parts of dibutyltin dilaurate, and 35 parts of diphenylmethane diisocyanate were mixed, stirred evenly, heated to 92°C, reacted for 4-5 hours, and cooled to room temperature to obtain polyurethane epoxy resin;
[0053] S2: 110 parts of 3-(carboxymethyl)benzoic acid and 260 parts of 4,7,10-trioxytridecyl-1,13-diamine were mixed, heated to 210°C with stirring, reacted for 4.5 hours, and distilled under reduced pressure until no obvious bubbles were present. The reaction was stopped and cooled to room temperature to obtain a rigid polyetheramine;
[0054] S3: 10 parts of polyurethane epoxy resin and 95 parts of rigid polyetheramine were mixed, heated to 85° C. with stirring, reacted for 4.5 hours, and cooled to room temperature to obtain a modified curing agent.
[0055] Comparative Example 1: The curing agent is not modified, and a polyetheramine curing agent is used. The rest is the same as Example 3, as follows:
[0056] Step 1: 14.5 parts of ferric chloride hexahydrate, 14 parts of PEO-PPO-PEO, and 360 parts of deionized water were mixed and stirred evenly, and then 27 parts of glacial acetic acid, 5.5 parts of terephthalic acid, and 4.5 parts of 2-aminoterephthalic acid were added, and the mixture was stirred evenly, and then heated to 115°C, kept warm for 12.5 hours, cooled, centrifuged, washed, and vacuum dried to obtain an iron-based MOF powder;
[0057] Step 2: Dissolve 8 parts of zirconium chloride in 75 parts of N,N-dimethylformamide, add concentrated hydrochloric acid to adjust the acidity of the reaction system, and stir ultrasonically until completely dissolved. Then, add 6.5 parts of 2-aminoterephthalic acid and 3.5 parts of iron-based MOF powder, stir evenly, heat to 85°C, react for 24 hours, cool to room temperature, and centrifuge to obtain dual MOF powder;
[0058] Step 3: Add 0.8 parts of dual MOF powder to 1 part of water-based epoxy resin emulsion, apply it to the surface of glass fiber, and cure it at 60°C for 24 hours to obtain a glass fiber semi-finished product, and combine and bond them, and roll them into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent; the water-based epoxy resin emulsion includes the following substances: 80 parts of water-based epoxy emulsion (GS-730A), 100 parts of curing agent, 3 parts of γ-glycidyloxypropyltrimethoxysilane, and 30 parts of water.
[0059] Comparative Example 2: Instead of preparing a dual MOF, a simple iron-based MOF was prepared, and the rest was the same as Example 3, specifically as follows:
[0060] Step 1: 14.5 parts of ferric chloride hexahydrate, 14 parts of PEO-PPO-PEO, and 360 parts of deionized water were mixed and stirred evenly, and then 27 parts of glacial acetic acid, 5.5 parts of terephthalic acid, and 4.5 parts of 2-aminoterephthalic acid were added, and the mixture was stirred evenly, and then heated to 115°C, kept warm for 12.5 hours, cooled, centrifuged, washed, and vacuum dried to obtain an iron-based MOF powder;
[0061] Step 2: Add 0.8 parts of iron-based MOF powder to 1 part of water-based epoxy resin emulsion, apply it to the surface of glass fiber, and cure it at 60°C for 24 hours to obtain a glass fiber semi-finished product, and combine and bond them, and roll them into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent; the water-based epoxy resin emulsion includes the following substances: 80 parts of water-based epoxy emulsion (GS-730A), 100 parts of modified curing agent, 3 parts of γ-glycidyloxypropyltrimethoxysilane, and 30 parts of water;
[0062] Wherein, the preparation process of the modified curing agent is:
[0063] S1: 65 parts of epoxy resin 6101, 42 parts of polyethylene glycol, 0.15 parts of dibutyltin dilaurate, and 35 parts of diphenylmethane diisocyanate were mixed, stirred evenly, heated to 92°C, reacted for 4-5 hours, and cooled to room temperature to obtain polyurethane epoxy resin;
[0064] S2: 110 parts of 3-(carboxymethyl)benzoic acid and 260 parts of 4,7,10-trioxytridecyl-1,13-diamine were mixed, heated to 210°C with stirring, reacted for 4.5 hours, and distilled under reduced pressure until no obvious bubbles were present. The reaction was stopped and cooled to room temperature to obtain a rigid polyetheramine;
[0065] S3: 10 parts of polyurethane epoxy resin and 95 parts of rigid polyetheramine were mixed, heated to 85° C. with stirring, reacted for 4.5 hours, and cooled to room temperature to obtain a modified curing agent.
[0066] Comparative Example 3: The amount of the double MOF was increased, and the rest was the same as Example 3, as follows:
[0067] Step 1: 14.5 parts of ferric chloride hexahydrate, 14 parts of PEO-PPO-PEO, and 360 parts of deionized water were mixed and stirred evenly, and then 27 parts of glacial acetic acid, 5.5 parts of terephthalic acid, and 4.5 parts of 2-aminoterephthalic acid were added, and the mixture was stirred evenly, and then heated to 115°C, kept warm for 12.5 hours, cooled, centrifuged, washed, and vacuum dried to obtain an iron-based MOF powder;
[0068] Step 2: Dissolve 8 parts of zirconium chloride in 75 parts of N,N-dimethylformamide, add concentrated hydrochloric acid to adjust the acidity of the reaction system, and stir ultrasonically until completely dissolved. Then, add 6.5 parts of 2-aminoterephthalic acid and 3.5 parts of iron-based MOF powder, stir evenly, heat to 85°C, react for 24 hours, cool to room temperature, and centrifuge to obtain dual MOF powder;
[0069] Step 3: Add 4 parts of double MOF powder to 1 part of water-based epoxy resin emulsion, apply it to the surface of glass fiber, and cure it at 60°C for 24 hours to obtain a glass fiber semi-finished product, and combine and bond them, and roll them into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent; the water-based epoxy resin emulsion includes the following substances: 80 parts of water-based epoxy emulsion (GS-730A), 100 parts of modified curing agent, 3 parts of γ-glycidyloxypropyltrimethoxysilane, and 30 parts of water;
[0070] Wherein, the preparation process of the modified curing agent is:
[0071] S1: 65 parts of epoxy resin 6101, 42 parts of polyethylene glycol, 0.15 parts of dibutyltin dilaurate, and 35 parts of diphenylmethane diisocyanate were mixed, stirred evenly, heated to 92°C, reacted for 4-5 hours, and cooled to room temperature to obtain polyurethane epoxy resin;
[0072] S2: 110 parts of 3-(carboxymethyl)benzoic acid and 260 parts of 4,7,10-trioxytridecyl-1,13-diamine were mixed, heated to 210°C with stirring, reacted for 4.5 hours, and distilled under reduced pressure until no obvious bubbles were present. The reaction was stopped and cooled to room temperature to obtain a rigid polyetheramine;
[0073] S3: 10 parts of polyurethane epoxy resin and 95 parts of rigid polyetheramine were mixed, heated to 85° C. with stirring, reacted for 4.5 hours, and cooled to room temperature to obtain a modified curing agent.
[0074] Comparative Example 4: A commercially available domestic zeolite wheel was used as a low-boiling point VOCs adsorbent.
[0075] Detection experiment 1: A high-concentration pure solution of VOCs gas is placed in a gas washing bottle for bubbling to obtain a simulated exhaust gas source. The gas passes through the samples of the embodiment and the comparative example, and the VOCs are intercepted and adsorbed. Clean air is discharged from the outlet. The adsorption test is carried out at room temperature and pressure. VOCs with strong polarity and low boiling point are selected as representative pollutants, and the penetration time of the rotor is monitored by a portable VOCs detector;
[0076] Test experiment 2: The samples obtained in the embodiment and the comparative example were placed in a high airflow impact device for 24 hours, and then the same experiment as the test experiment 1 was carried out. The results are shown in the following table:
[0077]
[0078]
[0079] Table 1
[0080] Conclusion: The example successfully prepared a MOF rotor by compounding an iron-based MOF with a zirconium-based MOF and fixing it on the surface of glass fiber using a modified binder. Among them, Example 3, as the best example, significantly improved the adsorption capacity and selectivity of VOCs with strong polarity and low boiling point compared with the traditional zeolite rotor in Comparative Example 4. In addition, the application of the modified binder effectively enhanced the bonding force between the MOF and the rotor, so that the performance degradation rate caused by powder shedding under high airflow impact conditions was greatly reduced. In contrast, in Comparative Example 1, the curing agent was not modified, resulting in insufficient binder performance, which in turn reduced the bonding force, caused powder shedding, and affected the overall performance. In Comparative Example 2, the iron-based MOF was simply prepared without the zirconium-based MOF with a rigid structure, which limited its structural stability and adsorption performance, resulting in performance degradation. In Comparative Example 3, the amount of dual MOF powder used was too much, resulting in excessive filling of the pore structure, reducing the specific surface area and porosity of the material, thereby affecting the adsorption performance.
[0081] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a low-boiling-point VOCs adsorbent based on MOF, characterized in that: The following steps are involved: Step 1: Mix ferric chloride hexahydrate, PEO-PPO-PEO and deionized water, stir evenly, then add glacial acetic acid, terephthalic acid and 2-aminoterephthalic acid, continue to stir evenly, heat to 110-120°C, keep warm for 12-13h, cool, centrifuge, wash and vacuum dry to obtain iron-based MOF powder; Step 2: Dissolve zirconium chloride in N,N-dimethylformamide, add concentrated hydrochloric acid to adjust the acidity of the reaction system, stir ultrasonically until completely dissolved, then add 2-aminoterephthalic acid and iron-based MOF powder, stir evenly, heat to 80-90°C, react for 24-25h, cool to room temperature, and centrifuge to obtain dual MOF powder; Step 3: Add the dual MOF powder to the water-based epoxy resin emulsion, apply it to the surface of the glass fiber, and solidify it to obtain a glass fiber semi-finished product, which is then combined and bonded and rolled into a rotating wheel with a honeycomb structure to obtain a VOCs adsorbent.
2. The method for preparing a low-boiling-point VOCs adsorbent based on MOF according to claim 1, characterized in that: The iron-based MOF powder comprises the following substances: ferric chloride hexahydrate, PEO-PPO-PEO, deionized water, glacial acetic acid, terephthalic acid, and 2-aminoterephthalic acid, in parts by weight.
3. The method for preparing a low-boiling-point VOCs adsorbent based on MOF according to claim 1, characterized in that: The dual MOF powder comprises the following substances: zirconium chloride, N,N-dimethylformamide, 2-aminoterephthalic acid, and iron-based MOF powder in parts by weight.
4. The method for preparing a low-boiling-point VOCs adsorbent based on MOF according to claim 1, characterized in that: The mass ratio of the dual MOF powder to the water-based epoxy resin emulsion is (0.8-0.9):
1.
5. The method for preparing a low-boiling-point VOCs adsorbent based on MOF according to claim 1, characterized in that: The waterborne epoxy resin emulsion comprises the following substances: by weight, 80-90 parts of waterborne epoxy emulsion, 100-110 parts of modified curing agent, 3-6 parts of coupling agent, and 30-60 parts of water.
6. The method for preparing a low-boiling-point VOCs adsorbent based on MOF according to claim 5, characterized in that: The preparation process of the modified curing agent is: S1: Mix epoxy resin 6101, polyethylene glycol, dibutyltin dilaurate and diphenylmethane diisocyanate, stir evenly, heat to 90-95°C, react for 4-5h, and cool to room temperature to obtain polyurethane epoxy resin; S2: 3-(carboxymethyl)benzoic acid and 4,7,10-trioxytridecyl-1,13-diamine were mixed, stirred and heated to 200-220°C, reacted for 4-5h, and distilled under reduced pressure until no obvious bubbles were found, the reaction was stopped, and cooled to room temperature to obtain a rigid polyetheramine; S3: Mix the polyurethane epoxy resin and the rigid polyetheramine, stir and heat to 80-90°C, react for 4-5 hours, and cool to room temperature to obtain a modified curing agent.
7. The method for preparing a low-boiling-point VOCs adsorbent based on MOF according to claim 6, characterized in that: The polyurethane epoxy resin comprises the following substances: by weight, 60-70 parts of epoxy resin 6101, 40-45 parts of polyethylene glycol, 0.1-0.2 parts of dibutyltin dilaurate, and 30-40 parts of diphenylmethane diisocyanate; The rigid polyetheramine comprises the following substances: 100-120 parts by weight of 3-(carboxymethyl)benzoic acid and 250-280 parts by weight of 4,7,10-trioxytridecyl-1,13-diamine; The mass ratio of the polyurethane epoxy resin to the rigid polyetheramine in the modified curing agent is 1:(9-10).
8. The method for preparing a low-boiling-point VOCs adsorbent based on MOF according to claim 1, characterized in that: The curing process parameters are: temperature of 50-60° C. and time of 24-30 hours.
9. A VOCs adsorbent obtained according to the method for preparing a MOF-based low-boiling-point VOCs adsorbent according to any one of claims 1 to 8.